P. vivax malaria presenting as shock an unusual manifestation: Case series - Archana Kashyap; Anju Aggarwal; Deepika Harit; Gunvant Singh Eske (International Journal of Medical Research and Review, 2015)
Shock as a manifestation of Plasmodium vivax infection is rarely reported. Four children aged 8 – 12 years with severe vivax malaria presented with shock. Thrombocytopenia was detected in all cases. There were no bleed from any site. Diagnosis of P. vivax was made by blood smear and rapid diagnostic tests. All patients did not responded to initial fluid boluses and improved on steroid and anti malarial therapy being artesunate combination therapy.